The 372 T/C genetic polymorphism of TIMP-1 is associated with serum levels of TIMP-1 and survival in patients with severe sepsis - Lorente, Leonardo (BioMed Central, 2013)
INTRODUCTION: Previous studies have found higher circulating levels of tissue inhibitor of matrix metalloproteinase (TIMP)-1 in nonsurviving septic patients than in surviving septic patients, and an association between the 372 T/C genetic polymorphism of TIMP-1 and the risk of developing certain diseases. However, the relationship between genetic polymorphisms of TIMP-1, circulating TIMP-1 levels and survival in patients with severe sepsis has not been examined, and this was the objective of the study. METHODS: This multicentre, prospective, observational study was carried out in six Spanish ICUs. We determined the 372 T/C genetic polymorphism of TIMP-1 (rs4898), serum levels of TIMP-1, matrix metalloproteinase (MMP)-9, MMP-10, TNFα, IL-10 and plasma plasminogen activator inhibitor-1 (PAI-1). Survival at 30 days from ICU admission was the endpoint assessed. The association between continuous variables was carried out using Spearman's rank correlation coefficient or Spearman's rho coefficient. Multivariate logistic regression analysis was applied to determine the association between the 372 T/C genetic polymorphism and survival 30 days from ICU admission. RESULTS: Of 275 patients with severe sepsis, 80 had genotype CC, 55 had genotype CT and 140 had genotype TT of the 372 T/C genetic polymorphism of TIMP-1. Patients with the T allele showed higher serum levels of TIMP-1 than patients without the T allele (P = 0.004). Multiple logistic regression analysis showed that the T allele was associated with higher mortality at 30 days (odds ratio = 2.08; 95% confidence interval = 1.06 to 4.09; P = 0.03). Survival analysis showed that patients with the T allele presented lower 30-day survival than patients without the T allele (χ(2 )= 5.77; P = 0.016). We found an association between TIMP-1 levels and levels of MMP-9 (ρ = -0.19; P = 0.002), MMP-10 (ρ = 0.55; P <0.001), TNFα (ρ = 0.56; P <0.001), IL-10 (ρ = 0.48; P <0.001) and PAI-1 (ρ = 0.49; P <0.001). CONCLUSION: The novel findings of our study are that septic patients with the T allele in the 372 T/C genetic polymorphism of TIMP-1 showed higher serum TIMP-1 levels and lower survival rate. The determination of the 372 T/C genetic polymorphism of TIMP-1 thus has prognostic implications and could help in the selection of patients who may benefit from modulation of the MMP/TIMP balance.